2021
DOI: 10.1002/mnfr.202001170
|View full text |Cite
|
Sign up to set email alerts
|

Xanthohumol Microbiome and Signature in Healthy Adults (the XMaS Trial): Safety and Tolerability Results of a Phase I Triple‐Masked, Placebo‐Controlled Clinical Trial

Abstract: Scope: Xanthohumol, a prenylflavonoid from hops, has been extensively studied preclinically but has undergone limited research in human subjects. A triple-masked, placebo-controlled phase I clinical trial was conducted to examine the safety and tolerability of xanthohumol. Methods and Results: Thirty healthy volunteers were randomized to 24 mg day −1 xanthohumol (99.8% pure) or placebo for eight weeks. Comprehensive metabolic panels, complete blood counts, body weight, vital signs, and health-related quality o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 26 publications
2
25
0
Order By: Relevance
“…• Half-lives exceeded 20 h. Bradley et al [57] and Langley et al [58] RCT total xanthohumol (after enzyme hydrolysis of conjugates) with maximum concentrations (C max ) of 4.4 ng mL −1 reached after 3.8 h, 22.2 ng mL −1 reached after 3.6 h, and 27.6 ng mL −1 reached after 1.8 h, respectively. [45] The low bioavailability of xanthohumol in animals and humans may be a result of very limited uptake in the small intestine and rapid metabolization by microorganisms in the colon [11] as well as rapid and almost complete biotransformation in the small intestine and liver (see next paragraph).…”
Section: Bioavailability Of Orally Administered Xantohumolmentioning
confidence: 99%
See 4 more Smart Citations
“…• Half-lives exceeded 20 h. Bradley et al [57] and Langley et al [58] RCT total xanthohumol (after enzyme hydrolysis of conjugates) with maximum concentrations (C max ) of 4.4 ng mL −1 reached after 3.8 h, 22.2 ng mL −1 reached after 3.6 h, and 27.6 ng mL −1 reached after 1.8 h, respectively. [45] The low bioavailability of xanthohumol in animals and humans may be a result of very limited uptake in the small intestine and rapid metabolization by microorganisms in the colon [11] as well as rapid and almost complete biotransformation in the small intestine and liver (see next paragraph).…”
Section: Bioavailability Of Orally Administered Xantohumolmentioning
confidence: 99%
“…[44,45] A recently published placebo-controlled clinical trial (the XMaS Trial) confirmed the safety of xanthohumol given at daily doses of 24 mg for 8 weeks with all clinical biomarkers and anthropometrics being unaffected and/or staying within the clinically normal reference ranges. [57,58] Toxicological studies in mice indicate that even higher dosages and longer intakes of xanthohumol do not cause harm. Neither ad libitum intake of drinking water with 0.5 mmol L −1 xanthohumol for 4 weeks, nor daily feeding of about 1000 mg xanthohumol kg −1 body weight for 3 weeks impaired major organ functions.…”
Section: Safety Profile Of Xantohumolmentioning
confidence: 99%
See 3 more Smart Citations